2013
DOI: 10.1097/mpg.0b013e31828dc35d
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Vaccination in Central Europe

Abstract: Each year, rotavirus (RV) infection is the leading cause of acute gastroenteritis requiring hospitalisation and of nosocomially transmitted diseases in children younger than 5 years across Central European Vaccination Awareness Group (CEVAG) countries; however, inadequate surveillance systems and lack of routine RV testing still exist in most CEVAG countries, making it difficult to accurately assess the present burden of acute RV gastroenteritis in the younger population. Furthermore, routine immunisation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These hospital-based studies performed between 2005 and 2008 reported that 28%-43% of the incidence of AGE and at least a third of all the hospitalizations of children less than five years old could be attributed to RV. 15,16 Overall, only 6.3% of the children in the study were hospitalized, 20.1% of the RVpositive and 1.5% of the RV-negative.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These hospital-based studies performed between 2005 and 2008 reported that 28%-43% of the incidence of AGE and at least a third of all the hospitalizations of children less than five years old could be attributed to RV. 15,16 Overall, only 6.3% of the children in the study were hospitalized, 20.1% of the RVpositive and 1.5% of the RV-negative.…”
Section: Discussionmentioning
confidence: 94%
“…The existing incidence data for Bulgaria are based on hospitalized cases [15][16][17] but they include only the more severe cases and do not give an accurate impression of the epidemiology and actual burden of RV disease. By one estimate, up to one in five AGE cases will see a physician and no more than two percent will be admitted to a hospital or present to an emergency room while the remaining cases will be cared for in their home by the parents or other caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…25 Not yet included in the NIP, but the Romanian MoH will begin a second campaign for vaccination of schoolgirls (>12 years, three doses). 26 Recommended (not mandatory) for 12-year-old girls, partially reimbursed. 27 Administered to all unvaccinated girls, and girls only vaccinated once previously.…”
Section: Children With Chronic Medical Conditionsmentioning
confidence: 98%
“…USA recommendations issued annually by the Advisory Committee on Immunization Practices (ACIP) are included for comparison. Exceptions to the mandatory or fully reimbursed immunizations are given in the footnotes (6,22,23,26,31,33) to TABLE 1.…”
Section: Why Vaccinate High-risk Groups?mentioning
confidence: 99%
See 1 more Smart Citation